Coronary artery plaque burden and calcium scores in healthy men adhering to long-term wine drinking or alcohol abstinence - da Luz,P.L. (2014)
Observational studies suggest there are clinical benefits to moderate red wine (RW) consumption. However, the effects on coronary vasculature and overall lifestyle are unclear. We investigated whether a lifestyle of regular long-term RW consumption is associated with changes in coronary plaque burden, calcium score, carotid intima/media thickness, endothelial function, and metabolic variables, compared with alcohol abstinence. Healthy volunteers were evaluated by coronary computed tomography angiography (CTA) as well as carotid and brachial artery ultrasound. Nutritional status, psychological status, and metabolic variables were assessed. The study included 101 drinkers [aged 58.9±7.3 years (means±SD)], from wine brotherhoods, and 104 abstainers, from Anglican, Evangelical and Catholic churches both in the city of São Paulo, Brazil. No significant differences in demographics were noted. Lesion prevalence per patient assessed by coronary CTA and classified as absent (0), 1-25, 26-49, and ≥50% stenosis was similar between groups. When analyzed by individual arteries, i.e., left anterior descending, circumflex, and right coronary, prevalence was also not different. On the other hand, calcium scores were higher among drinkers than abstainers (144.4±362.2 vs 122.0±370.3; P<0.01). However, drinkers reported less history of diabetes and exercised more. RW drinkers consumed 2127.9±387.7 kcal/day while abstainers consumed 1836.0±305.0 (P<0.0001). HDL cholesterol was significantly higher among drinkers compared to abstainers (46.9±10.9 vs 39.5±9.0 mg/dL; P<0.001), while fasting plasma glucose was lower (97.6±18.2 vs 118.4±29.6 mg/dL; P<0.02). Liver enzymes were normal in both groups. In conclusion, long-term wine drinkers displayed a similar plaque burden but greater calcium score than abstainers, despite a more atherogenic diet, and the mechanisms for the increased calcium scores in the former remain speculative.